Diverse landscape of dermatologic toxicities from small‐molecule inhibitor cancer therapy. (21st October 2021) - Seervai, Riyad N. H.; Cho, Woo Cheal; Chu, Emily Y.; Marques‐Piubelli, Mario L.; Ledesma, Debora A.; Richards, Kristen; Heberton, Meghan M.; Nelson, Kelly C.; Nagarajan, Priyadharsini; Torres‐Cabala, Carlos A.; Prieto, Victor G.; Curry, Jonathan L.
Abstract: Background: Advances in molecular biology and genetics have contributed to breakthrough treatments directed at specific pathways associated with the development of cancer. Small‐molecule inhibitors (Nibs) aimed at a variety of cellular pathways have been efficacious; however, they are associated with significant dermatologic toxicities. Methods: We conducted a comprehensive review of dermatologic toxicities associated with Nibs categorized into the following five groups: (a) mitogen‐activated protein kinase; (b) growth factor/multi‐tyrosine kinase; (c) cell division/DNA repair; (d) signaling associated with myeloproliferative neoplasms; and (e) other signaling pathways. Prospective phase I, II, or III clinical trials, retrospective literature reviews, systematic reviews/meta‐analyses, and case reviews/reports were included for analysis. Results: Dermatologic toxicities reviewed were associated with every class of Nibs and ranged from mild to severe or life‐threatening adverse skin reactions. Inflammatory reactions manifesting as maculopapular, papulopustular/acneiform, and eczematous lesions were frequent types of dermatologic toxicities seen with Nibs. Squamous cell carcinoma with keratoacanthoma‐like features was associated with a subset of Nibs. Substantial overlap in dermatologic toxicities was found between Nibs. Conclusions: Dermatologic toxicities from Nibs are diverse and may overlap between classes of Nibs. Recognition of the various types of toxicities from Nibs is critical for patient care in the era of "oncodermatology/dermatopathology."